A quarter century of spectroscopic monitoring of the nearby M dwarf Gl 514: a super-Earth on an eccentric orbit moving in and out of the habitable zone - Damasso, Mario; Perger, M.; Almenara, J.M.; Nardiello, D.; Pérez-Torres, M.; Sozzetti, A.; Hara, N.C.; Quirrenbach, Andreas; Bonfils, X.; Osorio, M.R. Zapatero; Astudillo-Defru, N.; Hernández, J.I. González; et al. (Astronomy and astrophysics, 2022)
Context. Statistical analyses based on Kepler data show that most of the early-type M dwarfs host multi-planet systems consisting of Earth- to sub-Neptune-sized planets with orbital periods of up to ~250 days, and that at least one such planet is likely located within the habitable zone. M dwarfs are therefore primary targets to search for potentially habitable planets in the solar neighbourhood.Aims. We investigated the presence of planetary companions around the nearby (7.6 pc) and bright (V = 9 mag) early-type M dwarf Gl 514, analysing 540 radial velocities collected over nearly 25 yr with the HIRES, HARPS, and CARMENES spectrographs.Methods. The data are affected by time-correlated signals at the level of 2-3 m s−1 due to stellar activity, which we filtered out, testing three different models based on Gaussian process regression. As a sanity cross-check, we repeated the analyses using HARPS radial velocities extracted with three different algorithms. We used HIRES radial velocities and Hipparcos-Gaia astrometry to put constraints on the presence of long-period companions, and we analysed TESS photometric data.Results. We find strong evidence that Gl 514 hosts a super-Earth on a likely eccentric orbit, residing in the conservative habitable zone for nearly 34% of its orbital period. The planet Gl 514b has minimum mass mb sin ib = 5.2 ± 0.9 M⊕, orbital period Pb = 140.43 ± 0.41 days, and eccentricity eb = 0.45−0.14+0.15. No evidence for transits is found in the TESS light curve. There is no evidence for a longer period companion in the radial velocities and, based on astrometry, we can rule out a ~0.2 MJup planet at a distance of ~3-10 astronomical units, and massive giant planets and brown dwarfs out to several tens of astronomical units. We discuss the possible presence of a second low-mass companion at a shorter distance from the host than Gl 514 b.Conclusions. Gl 514 b represents an interesting science case for studying the habitability of planets on eccentric orbits. We advocate for additional spectroscopic follow-up to get more accurate and precise planetary parameters. Further follow-up is also needed to investigate the presence of additional planetary signals of less than 1 m s−1.
Gesehen am 10.01.2023